THE ECONOMIC EFFECT OF REJOSOPINGGIR UMKM ADVERTISEMENT IN VILLAGE WEBSITE - Siti Munawaroh; Zulva Zanna Kamila; Tamara Novianti Putri (International Journal Labs, 2022)
This study discusses the home business listed on the village website. In the home business there are several products, namely, anyaman bamboo, wedek, sesek and meri rejeki. The new Rejosopinggir website was created by researchers due to direct requests from village officials. The purpose of the website is to introduce village profiles and promote village superior products. In addition, many home-based businesses in Rejosopnggir village have not yet entered the social media scene to promote their products. Many home businesses are still using traditional methods for promotion. Examples include traveling throughout the village, approaching the nearest places or minimarkets, and disseminating products by word of mouth. According to Sombert's theory, the home business in Rejosopinggir is still in the first and second eras. Namely, a closed economy and crafts and barter. With this goal in mind, qualitative research is carried out by interviewing the four sources who come from superior products listed on the village website. This program is a forum for our research to become a benchmark for economic improvement in Rejosopinggir. From the results of the interviews, we have known the responses of the four businessmen in Rejosopinggir village. Three of the four interviewees stated that the results of the superior product profile could help them to expand the range of promotions for their products and attract more consumers. One of them thinks otherwise, namely the product profile on the village website needs a lot of improvement, especially in product information and product photos, because superior products always make new innovations. With interviews with the four sources, we can conclude that there are many rooms for improvement, especially the village's superior product menu, especially for detailed information about the local people's production sites as well as including complete product photos.